A DESCRIPTIVE ANALYSIS ON THE FUNCTION OF THE ORAL TRADITION MESSAGE KADA TOMINAA OF THE TORAJA TRIBE - Ratu, Ari; Luntungan, Grace; Liando, Meyske (SoCul: International Journal of Research in Social Cultural Issues, 2023)
The purpose of this article is to describe the functions of the oral tradition message Kada Tominaa from Tana Toraja. This study is conducted in the framework of qualitative method with the design of library research. The primary data source of this study is the Kada Tomina as an oral literature from Tana Toraja. The primary data is supported by the secondary data such as books, research papers and articles from varios academic journals. The data is collected using the note-taking technique and analyzed descriptively. The findings show that the oral tradition message of Kada Tomina has two important functions. The first function is to represent the expressive actions, such as expressing feelings. The second is to show the directive action messages, in the form of noble hopes and advice. The findings impliy that the oral tradition Kada Tominaa is integral part of the people of Tana Toraja.